Decentralisation, Participation and Boundaries of Transformation: Forest Rights Act, Wayanad, India - Sudheesh R. Chemmencheri (Commonwealth Journal of Local Governance, 2013)
Participation and decentralisation have been shown to yield democratic outcomes in terms of efficiency, accountability and transparency through citizen engagement and devolution of powers. It has been a matter of debate whether they also benefit marginalised communities like the indigenous peoples. This paper analyzes the implications of decentralised governance in a tribal zone in India using the case of the Scheduled Tribes and Other Traditional Forest Dwellers (Recognition of Forest Rights) Act 2006 − the Forest Rights Act. The effects of the Act are studied in the district of Wayanad, Kerala, through the theoretical framework of transformative decentralisation and spatial politics of participation. The key objectives of the Act − securing tenure and access to Minor Forest Produce − have achieved limited success in Wayanad as a result of a narrowly construed ideas of people’s participation. While the process prescribed by the Forest Rights Act has the potential to create new spaces for participation, most of these spaces remain closed in Wayanad. The absence of a larger vision and a radical motive to engage with the underlying patterns of domination and subordination in society has confined the process of decentralisation to its technocratic essentials, raising questions on the extent to which the Act can pave the way for transformation.